Vascular endothelial growth factor as a potential prognostic factor for T3N0 rectal cancer - Sekulić, Aleksandar; Barišić, Goran; Dundjerović, Duško; Tatić, Svetislav; Krivokapić, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. Rectal cancer still presents a major health problem. Although a surgery is the mainstay of the rectal cancer treatment, there is now widespread agreement that combined modality therapy is often indicated. Around 20% of T3N0 rectal cancer patients develop distant or local relapse of the disease. There is a need for prognostic biomarkers that could help us determine the subgroup of patients with a high risk for recurrence. The aim of this study was to determine the prognostic potential of vascular endothelial growth factor (VEGF) in patients with T3N0 rectal carcinoma. Methods. This retrospective study included 163 selected T3N0 rectal cancer patients, operated on the Department for Colorectal Surgery of the Clinic for Digestive Surger (First Surgical Clinic), Clinical Centre of Serbia, Belgrade. VEGF expression was immunohistochemically assessed. Oncological outcome was analyzed using data from prospectively designed data base. Parameters of interest were: distant metastases, the disease free and overall survival. Survival and time to recurrence were evaluated using Kaplan Meier`s method and the factors were compared with the long-rank test. Results. There were 102 men and 61 women. The median age was 62 years (age range, 31–88 years). Median follow-up interval was 81 months (range, 4–177 months). During the follow-up period 6 patients developed local recurrence, in 31 patients distant metastases occurred. Three factors were found to be associated with distant metastases: VEGF expression, mucinous adenocarcinoma and tumor differentiation (p
Keywords: biomarkers; prognosis; rectal neoplasms; recurrence; vascular endothelial growth factor